Parties and party systems in Pietro Grilli Di Cortona’s research - Castaldo, Antonino (2017)
Parties and party systems, intended as key democratic institutions, represented a central subject in Pietro Grilli di Cortona’s research. His focus on these topics has been rich, innovative and continuous during all his career. His approach to the study of political parties and party systems has always been comparative, with a great relevance given to their historical evolution and the connections with the cleavages structures present in European societies.